FACTORS MILITATING AGAINST THE STUDENT’S PARTICIPATION IN SPORTS, LEISURE AND RECREATIONAL ACTIVITIES IN UNIVERSITY OF BENIN - GABRIEL E. ARAINRU; CHUKWUMA SUNDAY LATOR (International Studies Journal)
The study investigated the factors militating against the students of University of Benin participation in sports, leisure and recreational activities. The study contributed to literature in the area of admonishing the government on the need to finance sports, recreation and leisure. The study differs from previous related studies in terms of the location/clime in which the study was carried out which could affect the study generally. The research design adopted for the research was the descriptive survey research design. The population for this study was 41,520 students of University of Benin. The random sampling technique was used in selecting 400 students for the research. A correlation co-efficient of 0.76 was obtained using Pearson’s correlation statistics. The data collected was analysed using simple percentages, tables and frequency counts. The finding from the study revealed that the time allotted for sports, recreation and leisure was not enough. It was also discovered that there were not enough facilities and equipment to carry-out the activities. It also revealed that there was no general time for students to participate in these activities. It was therefore, recommended that both the University authorities and Government at all levels should provide adequate and functional facilities and equipment for the activities to take its proper place. Also that a general day and time should be approved by the university management for these activities to take place. It was also recommended that the time should be enough for these activities.